Răspuns :
a). 4x^2 -1= (2x-1)(2x+1)
b). 9-16y^2= (3-4y)(3+4y)
c). (x+y)^2 -4= (x+y+2)(x+y-2)
d). 64a^2 -b^2= (8a-b)(8a+b)
e). xy-y^2= y(x-y)
f). a^4-x^2= (a^2 -x)(a^2 +x)
g). x^2-4xy+4y= (x+2y)^2
h). 2ab+b^3c= b(2a+b^2c) ...cred..
i). a^2+2a+1= (a+1)^2
j). 4x^2-4xy+y^2=(2x-y)^2
k). a^2+6a+9= (a+3)^2
l). (a+b)-(a+b)^2= (a+b)(1-a-b).
b). 9-16y^2= (3-4y)(3+4y)
c). (x+y)^2 -4= (x+y+2)(x+y-2)
d). 64a^2 -b^2= (8a-b)(8a+b)
e). xy-y^2= y(x-y)
f). a^4-x^2= (a^2 -x)(a^2 +x)
g). x^2-4xy+4y= (x+2y)^2
h). 2ab+b^3c= b(2a+b^2c) ...cred..
i). a^2+2a+1= (a+1)^2
j). 4x^2-4xy+y^2=(2x-y)^2
k). a^2+6a+9= (a+3)^2
l). (a+b)-(a+b)^2= (a+b)(1-a-b).